Educational level and risk profile and risk control in patients with coronary heart disease - Bruthans, Jan; Mayer, Otto; De Bacquer, D; De Smedt, D; Reiner, Z; Kotseva, K; Cífková, Renata (European journal of preventive cardiology, 2016)
BACKGROUND: The purpose of this study was to ascertain way in which conventional risk factors, readiness to modify behaviour and to comply with recommended medication, and the effect of this medication were associated with education in patients with established coronary heart disease (CHD). METHODS: The EUROASPIRE IV (EUROpean Action on Secondary Prevention by Intervention to Reduce Events) study was a cross-sectional survey undertaken in 24 European countries to ascertain how recommendations on secondary CHD prevention are being followed in clinical practice. Consecutive patients, men and women ≤80 years of age who had been hospitalized for an acute coronary syndrome or revascularization procedure, were identified retrospectively. Data were collected through an interview with examinations at least six months and no later than three years after hospitalization. RESULTS: A total of 7937 patients (1934 (24.37%) women) were evaluated. Patients with primary education were older, with a larger proportion of women. Control of risk factors, as defined by Joint European Societies 4 and 5 guidelines, was significantly better with higher education for current smoking (p = 0.001), overweight and obesity (p = 0.047 and p = 0.029, respectively), low physical activity (p < 0.001) and low high-density lipoprotein (HDL)-cholesterol (p = 0.011) in men, and for obesity (p = 0.005), high blood pressure (p < 0.005 and p < 0.001), low physical activity (p = 0.001), diabetes (p < 0.001) and low HDL-cholesterol (p = 0.023) in women. Patients with primary and secondary education were more often treated with diuretics and antidiabetic drugs. Better control of hypertension was achieved in patients with higher education. CONCLUSION: Particular risk communication and control are needed in secondary CHD prevention for patients with lower educational status.
Keywords: Risk Factors; rizikové faktory; Secondary Prevention; vzdělávání pacientů jako téma; sekundární prevence; Coronary Disease; Patient Education as Topic; koronární nemoc